Estimation of Cost and Return of Plantain Production in Orhionwon Local Government Area, Edo State, Nigeria - A. I. N, Kaine; Okoje, L. J. D (Asian Journal of Agriculture and Rural Development, 2014)
The study examined the cost and return of plantain production in Orhionmwon Local Government Area, Edo State. Multi-stage sampling procedure was used to select 40 plantain farmers from two clans in the study area. Data required for the study were generated using questionnaire and interview schedule. Information generated was coded and analyzed using descriptive statistics, gross margin analysis, t-ratio statistic and likert scale method. The finding shows that plantain production is a very profitable enterprise and that for every one naira invested in plantain production, there is a return on investment of about N12.60 kobo. The result shows that the farmers are relatively young with majority (90 percent) below 54 years of age. About 45 percent of farmers acquired formal education. The study indicates that both male and female were engaged in plantain production enterprise. Total cost of production was N37, 983 with the variable cost item as the major component while the fixed cost was (3,934). There was a net profit of N36, 421.70. The result also shows that plantain production is affected by farm size and also that output is corrected to farm size too.